Detection of cheese whey in raw milk preserved with bronopol® through high performance liquid chromatography - Lasmar, M.M.; Leite, M.O.; Fonseca, L.M.; Souza, M.R.; Cerqueira, M.M.O.P.; Penna, C.F.A.M.; Couto, C.N.B.; Ferreira, J.M. (Arquivo brasileiro de medicina veterinária e zootecnia, 2011)
High performance liquid chromatography was used in order to detect cheese whey in samples of raw milk preserved with Bronopol®. Six samples were collected and divided in 45 aliquots of 40mL. From these, 15 were used as control and stored frozen, 15 were added with Bronopol® and stored at 7ºC, and the other 15 were added with Bronopol® and stored at 30ºC. In all groups, five levels of cheese whey addition (0, 2, 5, 10, and 20%) were tested. The samples were submitted to high performance liquid chromatography on the 2nd, 4th, and 8th days of storage. A completely random design was used, following the factorial scheme (5x3x3) and the results were compared through the non-parametric Kruskal-Wallis test. There was no difference among the treatments (P>0.05), which allows the conclusion that raw milk preserved with Bronopol® may be used for the determination of cheese whey addition in milk through high performance liquid chromatography. O objetivo deste trabalho foi avaliar a viabilidade do uso de amostras de leite cru conservadas com Bronopol® na pesquisa de soro de queijo por cromatografia líquida de alta eficiência (CLAE). Seis amostras foram coletadas e subdivididas em 45 alíquotas de 40mL. Destas, 15 compuseram o grupo controle e foram armazenadas sob congelamento, 15 amostras foram adicionadas de Bronopol® e armazenadas a 7ºC e outras 15 foram adicionadas de bronopol e estocadas a 30º C. Em todos os grupos, cinco porcentagens de soro de queijo foram adicionados, 0, 2, 5, 10 e 20%. As amostras foram submetidas à cromatografia líquida de alta eficiência no segundo, quarto e oitavo dias de armazenamento. Foi utilizado o delineamento inteiramente ao acaso, com os tratamentos em esquema fatorial 5x3x3 e os resultados comparados por meio do teste não paramétrico de Kruskal Wallis. Não houve diferença (P>0,05) entre os tratamentos, concluindo-se que é possível utilizar amostras de leite cru conservadas com Bronopol® para pesquisa de soro de queijo em leite por CLAE.